Workload and working hours effect on employees work-life balance mediated by work stress - Natanael, Kevin; Iman Kalis, Maria Christiana; Daud, Ilzar; Rosnani, Titik; Fahruna, Yulyanti (Institute of Computer Science (IOCS), 2023)
Work-life balance and work stress is an important aspect to consider nowadays. A good work-life balance has a positive impact on employee productivity and well-being. However, high workload pressure and long working hours can disrupt that balance. This study aims to analyze the influence of Workload and working hours on employees work-life balance mediated by work stress. This research took place or objective at PT Perkebunan Nusantara XIII employees. PT Perkebunan Nusantara XIII is one of the state-owned companies. This research used descriptive quantitative research using the survey method with total 267 respondent. This study used a five-point Likert scale. In this study, measurement and analysis used Structural Equation Modeling (SEM) with AMOS 24 statistical tools. The results of this study indicate that only two hypotheses are accepted, and the remaining five hypotheses are rejected. This study shows that Workload has a positive and significant effect on Work-Life Balance, and Work Stress has a positive and significant effect on Work-Life Balance. Meanwhile, Workload negatively affects Work Stress, Working Hours negatively affect Work Stress, and Working Hours negatively affects Work-Life Balance. Work Stress does not intervene in the influence of Workload and Working Hours on Work-Life Balance